2007
DOI: 10.1029/2006jd008369
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐QBO interaction and its impact on stratospheric ozone in a zonally averaged photochemical transport model of the middle atmosphere

Abstract: [1] We investigate the solar cycle modulation of the quasi-biennial oscillation (QBO) in stratospheric zonal winds and its impact on stratospheric ozone with an updated version of the zonally averaged CHEM2D middle atmosphere model. We find that the duration of the westerly QBO phase at solar maximum is 3 months shorter than at solar minimum, a more robust result than in an earlier CHEM2D study due to reduced Rayleigh friction drag in the present version of the model. The modeled solar cycle ozone response, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 49 publications
9
51
0
Order By: Relevance
“…Dunkerton (2001) also observed a similar double peak structure in ozone, methane, and water vapor QBO anomalies derived from HALOE data. McCormack et al (2007) reported similar structure in SBUV data. Results of numerical simulation also reported two peaks of about 4% near 24 and 32 km (Chipperfield et al, 1994;Jones et al, 1998;McCormack et al, 2007).…”
Section: Spatiotemporal Variation Of the Ozone Qbo In The Subtropicssupporting
confidence: 65%
See 2 more Smart Citations
“…Dunkerton (2001) also observed a similar double peak structure in ozone, methane, and water vapor QBO anomalies derived from HALOE data. McCormack et al (2007) reported similar structure in SBUV data. Results of numerical simulation also reported two peaks of about 4% near 24 and 32 km (Chipperfield et al, 1994;Jones et al, 1998;McCormack et al, 2007).…”
Section: Spatiotemporal Variation Of the Ozone Qbo In The Subtropicssupporting
confidence: 65%
“…McCormack et al (2007) reported similar structure in SBUV data. Results of numerical simulation also reported two peaks of about 4% near 24 and 32 km (Chipperfield et al, 1994;Jones et al, 1998;McCormack et al, 2007). Kinnersley (1998) reported similar structure in equatorial zonal winds.…”
Section: Spatiotemporal Variation Of the Ozone Qbo In The Subtropicssupporting
confidence: 65%
See 1 more Smart Citation
“…The dominant feature observed around 30-50 hPa may be related to the connection between quasi-biennial oscillation (QBO) and solar activity. Some studies have in fact supported the solar influence on the lower stratosphere dynamics with the observed 11-year variation in the QBO in the stratospheric equatorial zonal winds (e.g., Labitzke, 2005;Soukharev and Hood, 2006;McCormack et al, 2007). Moreover, they showed that the combined effects of solar UV variations, the QBO and planetary wave forcing could provide a possible explanation for the 11-year ozone response in the tropical lower stratosphere, where the ozone distribution is largely controlled by transport.…”
Section: Relationship With the 11-year Solar Cyclementioning
confidence: 95%
“…The effect of the quasi-biennial oscillation (QBO) in easterly and westerly stratospheric winds in the tropics on stratospheric ozone is a well-established effect based on both observations and stratospheric modeling and is known to affect stratospheric ozone outside the tropics as well (McCormack et al, 2007;Witte et al, 2008;WMO 2010, chapter 2, and references therein). The QBO is represented by time series of monthly averaged wind speed measurements done by the ground station in Singapore (Baldwin et al, 2001).…”
Section: Qbomentioning
confidence: 99%